2018
DOI: 10.1016/j.aim.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Ramsey properties of nonlinear Diophantine equations

Abstract: We prove general sufficient and necessary conditions for the partition regularity of Diophantine equations, which extend the classic Rado's Theorem by covering large classes of nonlinear equations. Sufficient conditions are obtained by exploiting algebraic properties in the space of ultrafilters βN, grounding on combinatorial properties of positive density sets and IP sets. Necessary conditions are proved by a new technique in nonstandard analysis, based on the use of the relation of u-equivalence for the hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In this paper, we showed that Theorem 4 could be seen as a particular case of a more general characterization of partition regular equations 5 , that we proved by means of nonstandard methods. The same result is proven in [3] by means of purely standard methods based on ultrafilters. To introduce the result, we first need a definition: Definition 3 Let m be a positive natural number and let {y 1 , .…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…In this paper, we showed that Theorem 4 could be seen as a particular case of a more general characterization of partition regular equations 5 , that we proved by means of nonstandard methods. The same result is proven in [3] by means of purely standard methods based on ultrafilters. To introduce the result, we first need a definition: Definition 3 Let m be a positive natural number and let {y 1 , .…”
Section: Introductionsupporting
confidence: 65%
“…Proof This result can be proven following the same ideas of the proof of Theorem 3.3 in [9], if one wants to use nonstandard methods, or of Theorem 2.10 in [3], if one wants to use purely standard arguments based on ultrafilters. We adapt here the proof of Theorem 2.10 in [3] (which talked about the partition regularity on N and was more complicated as we handled also the injectivity properties of the sets of solutions of equation 3) to our present case. Let U be an idempotent ultrafilter in K (β(0, 1), ) or K (β S, ).…”
Section: Propositionmentioning
confidence: 96%
See 3 more Smart Citations